Fracture mechanics analysis of defence hole system for a uniaxially loaded plate using boundary element method - Chua, Benedict Yi Wenn (Nanyang Technological University, 2023)
This report studies the effects of elliptical defence hole systems on a main hole in a uniaxially loaded plate. This study was accomplished using the BIE2DSRE-A program which uses the Boundary Element Method (BEM), to obtain stress concentrations around the main hole and stress intensity factors (SIF) at the tip of a crack originating from the central main hole. Several elliptical Defence Hole System (DHS) configurations were modelled to determine which provides the greatest reduction in the Stress Concentration Factor (SCF). In previous DHS studies, the reduction in the SCF was explored by varying the diameter of the circular auxiliary hole. This study allows us to gain an understanding of the potential benefits or drawbacks of using an elliptical auxiliary hole in place of the traditional circular auxiliary hole.